1994
DOI: 10.1017/s0007485300032491
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and sampling of Chilo partellus (Lepidoptera: Pyralidae) in maize and sorghum on the Kenya coast

Abstract: The seasonal occurrence and spatial distribution of the crambine stem borer, Chilo partellus (Swinhoe) were investigated in maize, Zea mays, and sorghum, Sorghum bicolor, fields at the Kenya coast. During the vegetative growth stage, small-sized larvae were typically found behind leaf sheaths and in whorls in maize and sorghum. In reproductive and senescent maize, small-sized larvae were also found feeding in ears. Later immature life stages were located predominantly in stems in sorghum, and in the stems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 29 publications
(30 reference statements)
2
35
0
Order By: Relevance
“…Similar fi ndings were reported from C. partellus (Overholt et al 1994b), on B. fusca (Chabi-Olaye et al 2005b) and on S. calamistis (Schulthess et al 1991). Th e distributions become progressively less aggregated as insects aged (Overholt et al 1994b;Ndemah et al 2001b).…”
Section: Discussionsupporting
confidence: 80%
“…Similar fi ndings were reported from C. partellus (Overholt et al 1994b), on B. fusca (Chabi-Olaye et al 2005b) and on S. calamistis (Schulthess et al 1991). Th e distributions become progressively less aggregated as insects aged (Overholt et al 1994b;Ndemah et al 2001b).…”
Section: Discussionsupporting
confidence: 80%
“…Previous work indicated that despite the large numbers of parasitoids and relatively high parasitism levels by indigenous parasitoids of maize stemborers (Berger 1981;Gonçalves 1970;Kfi r 1995), the parasitoids are not able to prevent economic damage and/or reduce pest populations to below economic threshold levels (Kfi r 1997;2000;Overholt 1998;Overholt et al 1994). Th e present work, however, suggests that their impact on pest infestations and maize yield can be considerable.…”
Section: Discussionmentioning
confidence: 53%
“…Data for the short rains of 1996 was unavailable. The sampling methodology was described in Overholt et al (1994b). Plants were sampled starting at plant emergence up to senescence by excising and dissecting randomly selected plants from the field.…”
Section: Methodsmentioning
confidence: 99%